Preliminary evaluation of the decontaminating potential of a manganese oxide supported on mordenite - Vázquez-Rodríguez, Gabriela Alejandra; Trejo-Bustillos, Perla Rubí (Renewable Energy, Biomass & Sustainability, 2021)
The treatment and in situ reuse of greywater could greatly contribute to reduce the water demand at the municipal level, thereby achieving social, economic, and environmental benefits. Decentralized treatment systems use chemical, physical and biological methods to decontaminate water, which then allows its reuse in garden irrigation, filling toilets or cleaning without primary contact with the inhabitants of the home, among other uses. In several of these systems (such as submerged wetlands or biofilters), filter materials are used. For example, zeolites and manganese oxides (MnOx) are reported in the literature as excellent candidates for use in water treatment due to their adsorption properties and, in the case of the latter, to its oxidation potential. In this work, a coating with a manganese oxide was carried out through a precipitation reaction on mordenite-type zeolitic material, to be used as a filter material in decentralized greywater treatment systems. The synthetized composite material was analyzed by the methylene blue adsorption test and the experimental data was adjusted to the Langmuir Isotherm model. The value of the specific surface area of the MnOx-coated mordenite-type zeolite was also estimated. With this analysis, it was possible to obtain preliminary results about the capacity of this material to decontaminate household greywater, which needs to be confirmed by further research.